Development and validation of an emotional picture set of self-injury (EPSI) for borderline personality disorder: protocol for a validation study - Bachmann, Katharina; Schulze, Marcel; Sörös, Peter; Schmahl, Christian; Philipsen, Alexandra (BMJ open, 2019)
Introduction Borderline personality disorder (BPD) is a severe psychiatric disorder that is characterised by major problems in emotion regulation. Affected persons frequently engage in non-suicidal self-injury (NSSI) to regulate emotions. NSSI is associated with high emotionality in patients with BPD and it can be expected that stimuli depicting scenes of NSSI elicit an emotional response indicative of BPD. The present study protocol describes the development and validation of an emotional picture set of self-injury (EPSI) to advance future research on emotion regulation in BPD. - Methods and analysis The present validation study aims to develop and validate an emotional picture set relevant for BPD. Emotional responses to EPSI as well as to a neutral picture set will be investigated in a sample of 30 patients with BPD compared with 30 matched, healthy controls and to 30 matched depressive controls. Emotional responses will be assessed by heart rate variability, facial expression and Self-Assessment Manikin. - Ethics and dissemination Ethics approval was obtained by the medical ethics committee of the Carl-von-Ossietzky University of Oldenburg, Germany (registration: 2017-044). The results of the trial will be submitted for publication in a peer-reviewed journal. - Trial registration number NCT03149926; Pre-results.